Open-Label Adhesion Performance Study of a Prescription Lidocaine Topical System 1.8% versus Three Lidocaine-Containing Over-the-Counter Patches in Healthy Subjects - Fudin J; Vought K; Patel K; Lissin D; Maibach H (Journal of Pain Research, 2022)
Jeffrey Fudin,1– 3 Kip Vought,4 Kalpana Patel,4 Dmitri Lissin,4 Howard Maibach5 1Pain Management and PGY2 Pharmacy Pain Residency, Samuel Stratton Department of Veterans Affairs Medical Center, Albany, NY, USA; 2Remitigate Therapeutics, Delmar, NY, USA; 3Department of Pharmacy, Albany College of Pharmacy and Health Sciences, Albany, NY, USA; 4Clinical Development, Scilex Pharmaceuticals Inc, Palo Alto, CA, USA; 5Dermatology Department, University of California San Francisco, San Francisco, CA, USACorrespondence: Dmitri Lissin, Clinical Development, Scilex Pharmaceuticals Inc, 960 San Antonio Road, Palo Alto, CA, 94303, USA, Tel +1 650.516.4310, Email dlissin@scilexpharma.comPurpose: This study evaluates and compares the clinical adhesion performance of a prescription lidocaine topical system 1.8% versus two different over-the-counter (OTC) lidocaine patches 4% and an OTC combination menthol and lidocaine patch 1%/4% in human subjects.Patients and Methods: This study was an open-label, randomized, four-treatment, four-sequence, Phase 1 adhesion performance study in healthy adult volunteers (N = 24). Lidocaine topical system 1.8% (R) and the three OTC patch products (T1, T2, and T3) were separately applied for 12 hours. Adhesion of all products was scored at 0, 3, 6, 8, and 12 hours post-application.Results: There were no issues with the conduct of the study. Overall, the majority (≥ 59.1%) of subjects treated (“patched”) with the lidocaine topical system 1.8% (R) demonstrated ≥ 90% adhesion (FDA adhesion score 0) throughout the 12-hour administration period versus 27.3% of subjects treated with OTC lidocaine patch 4% (T1), 22.7% of subjects treated with OTC lidocaine patch 4% (T2), and 18.2% of subjects treated with OTC menthol/lidocaine patch 1%/4%. Only one subject (4.5%) treated with lidocaine topical system 1.8% was observed with < 75% adhesion (FDA adhesion score < 2) versus 11 (50.0%) and 10 (45.5%) for the two OTC lidocaine patches 4% (T1 and T2), respectively, and 13 (59.1%) subjects for the OTC menthol/lidocaine patch 1%/4%. There were no complete detachments observed for lidocaine topical system 1.8%, whereas 50.0% and 31.8% complete detachments were observed for the two OTC lidocaine patches 4% (T1 and T2), and 27.3% complete detachments were observed for the OTC menthol/lidocaine patch 1%/4%. No adverse events were observed for any of the treatments.Conclusion: Lidocaine topical system 1.8% demonstrated superior adhesion relative to the three lidocaine-containing OTC products over the 12-hour treatment period.Keywords: lidocaine topical system, lidocaine patch, menthol/lidocaine patch, over-the-counter, adhesion, postherpetic neuralgia, external analgesic